2021
DOI: 10.3390/cells10071724
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Is Expressed in Immune Cells That Infiltrate the Placenta in Infection-Associated Preterm Birth

Abstract: COVID-19 is associated with increased incidence of preterm birth (PTB). We assessed pathways by which SARS-CoV-2 could access the placenta. Placentae, from PTB with or without chorioamnionitis (ChA), or from term pregnancies (n = 12/13/group) were collected. Peripheral blood was collected from healthy pregnant women (n = 6). Second trimester placental explants (16–20 weeks, n = 5/group) were treated with lipopolysaccharide (LPS, to mimic bacterial infection) and ACE2, CCL2, IL-6/8 and TNFα mRNA was assessed. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 76 publications
1
18
0
Order By: Relevance
“…SARS-CoV-2 functional modulation of macrophages localized on chorioamniotic membranes has also been reported, resulting in a mild inflammatory response systemically and at the maternal-fetal interface mediated by IL-8, IL-10, and IL-15 ( 92 ). Accordingly, histopathologic findings of abnormal maternal or fetal vascular perfusion were detected in 46% and 35% of analyzed placentas, respectively ( 86 91 ). Thus, the virus can cause vascular injury leading to ischemic damage of the placenta, affecting the fetus even without a direct infection ( 86 91 ).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 99%
See 3 more Smart Citations
“…SARS-CoV-2 functional modulation of macrophages localized on chorioamniotic membranes has also been reported, resulting in a mild inflammatory response systemically and at the maternal-fetal interface mediated by IL-8, IL-10, and IL-15 ( 92 ). Accordingly, histopathologic findings of abnormal maternal or fetal vascular perfusion were detected in 46% and 35% of analyzed placentas, respectively ( 86 91 ). Thus, the virus can cause vascular injury leading to ischemic damage of the placenta, affecting the fetus even without a direct infection ( 86 91 ).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 99%
“…Looking more specifically to the maternal-fetal interface, studies using precision-cut slices (PCSs) have shown that SARS-CoV-2 infection of the human placenta results in complete replication cycles with the release of infectious virus (84). Interestingly, the placenta's susceptibility to SARS-CoV-2 replication was related to the expression of ACE2 and TMPRSS2 (84)(85)(86)(87)(88)(89)(90)(91). A recent study also showed that ACE2-positive circulating immune cells of pregnant women with COVID-19 and chorioamnionitis could transfer the SARS-CoV-2 virus to the placenta, thus increasing the chance of vertical transmission (91).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 99%
See 2 more Smart Citations
“…14 Infection via trafficked maternal cells has been suggested, as evidenced by an observed expression of ACE2 protein in infiltrating maternal cells in human placentas with chorioamnionitis. 15 However, it is of note that despite widely reported placental pathology in viraemic mothers, infection in the fetus has not been well characterised and does not seem to be a common feature of preterm birth in association with a confirmed infection in the mother. 16 Neonatal infection plausibly could occur either through an ascending infection through the vagina and cervical canal or during vaginal birth via direct infant contact with maternal virus.…”
Section: Introductionmentioning
confidence: 99%